Why robots should not be delegated with the decision to kill. Issue 2 (3rd April 2017) - Sharkey, Noel
ABSTRACT: The EPSRC first principle of robotics, "robots should not be designed solely or primarily to kill or harm humans, except in the interests of national security", is challenged in detail here. Focusing on security and armed conflict, arguments are marshalled against the principle on ethical, legal, technical and security grounds. A new principle is proposed that robots should never be delegated with the decision to apply violent force to humans.